A comparative analysis of optimization solvers. Issue 4 (4th July 2017) - Anand, Rimmi; Aggarwal, Divya; Kumar, Vijay
Abstract: Optimization software provides better design and development of optimization solutions for real-life problems. The software generates different solutions under different constraints. An attempt has been made to compare three well-known optimization solvers. The comparisons have been done in terms of capabilities and problem domain. The results reveal that CPLEX and GuRoBi provide competitive optimization solutions. However, CPLEX performs better than GuRoBi under high dimensionality problems. Besides this, CPLEX is able to solve Non-convex mixed integer quadratic problem.